City diplomacy as noncoercive statecraft : gaining power and influence through attraction - Amiri, Sohaela (Routledge, 2026)
This book presents a rigorously designed framework for city diplomacy as a tool to enhance a nation's international appeal, attraction, and influence. This book illustrates how attraction-based influence is generated, and why city diplomacy enhances national security and prosperity through international exchanges, collaborations, and dialogues.It provides a structured approach to guide policies, strategies, research, and analysis for city diplomacy and the broader field of international affairs.